2021
DOI: 10.1186/s12940-021-00755-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute health effects associated with satellite-determined cyanobacterial blooms in a drinking water source in Massachusetts

Abstract: Background The occurrence of cyanobacterial blooms in freshwater presents a threat to human health. However, epidemiological studies on the association between cyanobacterial blooms in drinking water sources and human health outcomes are scarce. The objective of this study was to evaluate if cyanobacterial blooms were associated with increased emergency room visits for gastrointestinal (GI), respiratory and dermal illnesses. Methods Satellite-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Future research in these areas should increase remote sensing studies to gain insights into environmental factors that influence disease outbreaks, distribution, and risk. This information is vital for disease surveillance, risk mapping, and informing public health interventions [113,114]. As sensor technology advances and integrates with other geospatial information, remote sensing would support the development of more comprehensive and predictive public health strategies for TW.…”
Section: Perspectivementioning
confidence: 99%
“…Future research in these areas should increase remote sensing studies to gain insights into environmental factors that influence disease outbreaks, distribution, and risk. This information is vital for disease surveillance, risk mapping, and informing public health interventions [113,114]. As sensor technology advances and integrates with other geospatial information, remote sensing would support the development of more comprehensive and predictive public health strategies for TW.…”
Section: Perspectivementioning
confidence: 99%
“… 90 A recent study estimated potential exposures to cyanobacteria cell concentrations using remote sensing data in the Greater Boston area, Massachusetts, and found significant associations between cyanobacteria and increased cases of respiratory illness-related emergency room visits, but not with gastrointestinal or dermal symptoms. 91 State- and national-level surveillance systems have been recently leveraged to track cyanoHABs and associated health impacts, 92 , 93 with findings suggesting that the population-level health impacts of HABs have been underestimated previously. Multiple cyanotoxins were detected in several of the HAB outbreaks.…”
Section: Human Health Effects and Mechanismsmentioning
confidence: 99%
“…Once inhaled, these metabolites can cause toxicity at the absorption site, or be mobilized to target organs causing adverse effects [12] , [15] . The U.S. Center for Disease Control Morbidity and Mortality Weekly Report has shown that harmful CBs are associated with increased emergency room visits for respiratory illnesses [16] , [17] , [18] , [19] . More importantly, toxic compounds absorbed into the olfactory epithelium can circumvent the blood brain barrier and gain direct access to the brain [20] .…”
Section: Introductionmentioning
confidence: 99%